Mergers and partial ownership - Øystein Foros; Hans Jarle Kind; Greg Shaffer (Center for Economic Studies and ifo Institute (CESifo), 2010)
In this paper we compare the profitability of a merger to the profitability of a partial ownership arrangement and find that partial ownership arrangements can be more profitable for the acquiring and acquired firm because they can result in a greater dampening of competition. We also derive comparative statics on the prices of the acquiring firm, the acquired firm, and the outside firms. In a dual context, we show that a cross-majority owner may have incentives to sell a fraction of the shares in one of the firms he controls to a silent investor who is outside the industry. Aggregate ex post operating profit in the two firms controlled by the cross-majority shareholder then increases, such that both the cross-majority shareholder and the silent investor will be better off with than without the partial divestiture.
Keywords: L13; L22; L82; 330; media economics; mergers; corporate control; financial control